Identification of novel benzimidazole derivatives as anti-Trypanosoma cruzi agents: solid-phase synthesis, structure–activity relationships and molecular docking studies. (October 2013) - Ríos, Natalia; Varela, Javier; Birriel, Estefania; González, Mercedes; Cerecetto, Hugo; Merlino, Alicia; Porcal, Williams
Background: In this paper, we report the solid-phase synthesis of 33 novel 1, 2, 5-tri-substituted benzimidazole derivatives and their in vitro activity on cruzipain and Trypanosoma cruzi epimastigotes.Results: Seven compounds were potent inhibitors of T. cruzi growth with IC50 values in the range 6–16 µM. Applying structure–activity relationships and principal component analysis strategies we were able to determine ring substituent effects and physicochemical properties that are important for the antichagasic activity of these novel derivatives, as well as get an insight into their possible mechanisms of action. Molecular docking studies revealed the binding orientation of the ligands in the active site of cruzipain providing new guidelines for the further design of better inhibitors.Conclusion: Compound2a constitute a promising hit compound for novel anti- T. cruzi agents showing that the benzimidazole scaffold may represent an interesting therapeutic alternative for the treatment of Chagas disease.